2006
DOI: 10.1128/aem.00868-06
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Buggy Creek Virus: Evidence for Multiple Clades in the Western Great Plains, United States of America

Abstract: We present the first detailed phylogenetic analysis of Buggy Creek virus (BCRV), a poorly known alphavirus with transmission cycles involving a cimicid swallow bug (Oeciacus vicarius) vector and cliff swallows (Petrochelidon pyrrhonota) and house sparrows (Passer domesticus) as the principal avian hosts. Nucleotide sequences of a 2,075-bp viral envelope glycoprotein-coding region, covering the entire PE2 gene, were determined for 33 BCRV isolates taken from swallow bugs at cliff swallow colonies in Nebraska an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 33 publications
(43 reference statements)
1
66
0
Order By: Relevance
“…It is a member of the western equine encephalomyelitis virus complex, a group that also includes Highlands J virus, WEEV, SINV, and Aura virus (Reisen and Monath, 1989;Strauss and Strauss, 1994). Buggy Creek virus, and the closely related Fort Morgan virus (likely a strain of BCRV; Pfeffer et al, 2006), are unusual in being one of the few alphaviruses routinely vectored by insects other than mosquitoes: the typical vector is the cimicid swallow bug (Hemiptera: Cimicidae: Oeciacus vicarius; Rush et al, 1980;Scott et al, 1984;Hopla et al, 1993;Brown et al, 2001). The hematophagous swallow bug is an ectoparasite primarily of the colonially nesting cliff swallow (Petrochelidon pyrrhonota).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a member of the western equine encephalomyelitis virus complex, a group that also includes Highlands J virus, WEEV, SINV, and Aura virus (Reisen and Monath, 1989;Strauss and Strauss, 1994). Buggy Creek virus, and the closely related Fort Morgan virus (likely a strain of BCRV; Pfeffer et al, 2006), are unusual in being one of the few alphaviruses routinely vectored by insects other than mosquitoes: the typical vector is the cimicid swallow bug (Hemiptera: Cimicidae: Oeciacus vicarius; Rush et al, 1980;Scott et al, 1984;Hopla et al, 1993;Brown et al, 2001). The hematophagous swallow bug is an ectoparasite primarily of the colonially nesting cliff swallow (Petrochelidon pyrrhonota).…”
Section: Introductionmentioning
confidence: 99%
“…Buggy Creek virus (BCRV) is a poorly known alphavirus found widely in the western Great Plains of North America (Pfeffer et al, 2006). It is a member of the western equine encephalomyelitis virus complex, a group that also includes Highlands J virus, WEEV, SINV, and Aura virus (Reisen and Monath, 1989;Strauss and Strauss, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Buggy Creek virus, also known as Fort Morgan virus (FMV;Calisher et al, 1988;Pfeffer et al, 2006;Padhi et al, 2008), is a unique alphavirus in the WEEV antigenic complex. Although BCRV shares structural similarities with other alphaviruses in the WEEV complex, it is primarily transmitted by the cimicid swallow bug (Hemiptera: Cimicidae, Oeciacus vicarius), rather than by mosquitoes, and is not considered a pathogen of humans or domesticated animals (Griffin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Fort Morgan virus (Calisher et al, 1980), also found in swallow bugs, is a strain of BCRV (Pfeffer et al, 2006;Padhi et al, 2008); thus, FMV and BCRV are synonymous. Stone Lakes virus, recently isolated from California, is probably also a strain of BCRV (Brault et al, 2009).…”
Section: Study Organismsmentioning
confidence: 99%